1989
DOI: 10.1002/ajmg.1320330206
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia of the tibia with bifurcation of the femur and ectrodactyly: Evidence for an autosomal recessive type

Abstract: Two unrelated families are presented, each with 2 affected offspring with bifid femur, absent tibia, and ectrodactyly. The healthy parents are consanguineous. It is postulated that this combination of malformations is causally heterogenous with both autosomal dominant and autosomal recessive modes of inheritance; hence, it is established as a developmental field defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 7 publications
0
26
0
1
Order By: Relevance
“…In the family reported here, the parents were consanguineous, but in the Arab population the rate of consanguinity is high [Teebi and Farag, 1997], therefore consanguinity represents only a weak argument in favor of autosomal recessive inheritance. Nevertheless, many of the previously reported families [Majewski et al, 1985], the two consanguineous families reported by Kohn et al [1989] and the family reported here, are Arab Muslim families from the same geographic area. Therefore, the existence of an autosomal recessive gene must be considered [Majewski et al, 1996].…”
Section: Discussionmentioning
confidence: 66%
“…In the family reported here, the parents were consanguineous, but in the Arab population the rate of consanguinity is high [Teebi and Farag, 1997], therefore consanguinity represents only a weak argument in favor of autosomal recessive inheritance. Nevertheless, many of the previously reported families [Majewski et al, 1985], the two consanguineous families reported by Kohn et al [1989] and the family reported here, are Arab Muslim families from the same geographic area. Therefore, the existence of an autosomal recessive gene must be considered [Majewski et al, 1996].…”
Section: Discussionmentioning
confidence: 66%
“…Wolfgang [ 19841 published a typically affected offspring of healthy Amish parents, known to be mostly consanguineous. This high rate of consanguinity might hint at a recessive type of tibia1 aplasia with ectrodactyly, as suggested by Kohn et al [1989] and other authors. The consanguineous parents originated from Palestine [Der Kaloustian and Mnaymneh, 19731, Iran [Emami-Ahari and Mahloudji, 1974;Mahloudji and Farpour, 19741, Syria [Majewski et al, 19851, Brazil [Richieri-Costa, 1987a,cl, Saudi-Arabia [Mufti and Wood, 19871, Arabia [Kohn et al, 19891, Turkey [Sener et al, 1989, 19901, and Algeria (this report).…”
Section: Discussionmentioning
confidence: 80%
“…However, the same authors published on a consanguineous and healthy couple from Syria, who had three affected children. A total of 17 families with 39 affected sibs and normal parents have been described [White and Baker, 1888;Schwarzweller, 1939;Takahashi et al, 1968;Emami-Ahari and Mahloudji, 1974;Fried et al, 1977;Gollop et al, 1980;Kapur et al, 1982;Lenz, 1982;McKay et al, 1984;Majewski et al, 1985;RichieriCosta et al, 1987b,c;Mufti and Wood, 1987;Kohn et al, 1989;Sener et al, 1990;this report]. Further single cases with consanguineous parents were reported by Der Kaloustian and Mnaymneh [1973], Mahloudji and Farpour [ 19741, Richieri-Costa [1987al, and Sener et al [ 19891.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sıklıkla ailesel geçiş söz konusudur ancak kalıtım tipi net değildir. Çeşitli çalışmalarda otozomal dominant, otozomal resesif ve X'e bağlı geçişler tanımlanmıştır (6). Literatürde 100'den fazla sporadik olgu ile birlikte yaklaşık 50 kadar SHFLD'li aile tanımlanmıştır.…”
Section: Introductionunclassified